CAREGIVERS’ ATTITUDES AND UNDERSTANDING OF PERSONAL MENTAL HEALTH RECOVERY: THE INFLUENCE OF CULTURAL BELIEFS, STIGMA, AND CAREGIVING PRACTICES - Oktyabrova, Nurdana (Nazarbayev University School of Medicine, 2025)
Introduction: Caregivers play a crucial role in the recovery journey, and their perspectives are often overlooked in research. It is little known about their understanding and experience of personal mental health recovery, with focus on how cultural beliefs, stigma, and caregiving practices shape their journey. This is particularly true in the context of Kazakhstan, where these influences pay a powerful role in shaping both attitude and actions. Objectives: (1) To examine caregivers’ understanding and definitions of mental health recovery, focusing on the personal dimensions of recovery; (2) To investigate how caregivers’ attitudes toward mental health recovery affect their caregiving practices; (3) To explore the impact of cultural beliefs and societal stigma on caregivers’ attitudes, and how these factors shape their approach to supporting recovery; (4) To identify the types of support system (e.g., family, friends, professionals) that caregivers rely on and assess their availability and accessibility. Methods: A qualitative research was conducted, using semi-structured in-depth interviews with 8 caregivers of individuals living with mental health conditions (e.g., depression, bipolar disorder, autism, schizophrenia). Participants were recruited from community mental health centers (e.g., Kunde Cafe and the Orda Center), and through social networks using purposeful sampling. All interviews were conducted online. A mixed-method (inductive-deductive) thematic analysis was used. Results & Discussions: Through an inductive-deductive thematic analysis, 5 key themes emerged: understanding of recovery,caregiver attitudes, cultural influences, stigma, and personal growth. The findings revealed that caregiving is not only an act of support, but also a deeply emotional and transformative journey. In Kazakh culture, many caregivers initially faced silence, shame, and unrealistic expectations. However, gradually found strength through acceptance, emotional openness, and advocacy. Gender roles and societal pressures significantly influenced how caregiving responsibilities were assigned and experienced. Despite challenges, caregivers became informal educators and advocates, working to reduce stigma and raise awareness about mental health within their communities. Conclusion: The study aimed to understand how informal caregivers in Kazakhstan perceive and navigate the mental health recovery journey of their loved ones. It revealed that recovery is seen not as a final goal, but as an ongoing and deeply personal process shaped by emotions, cultural values, and societal pressures. Cultural and spiritual beliefs offered both comfort and constraint, while stigma continued to limit open conversation and help-seeking. Despite these challenges, many caregivers experienced personal growth, becoming advocates for mental health and recognizing the importance of caring for themselves, too. There is a need for culturally sensitive mental health support systems that recognize caregivers as essential partners in recovery. The insights offer valuable implications for public awareness, caregivers resources, and mental health policy.
Keywords: Embargo; Informal caregivers; Personal mental health recovery; The CHIME model; Cultural expectations; Stigma